PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA - Ade Jaya Sutisna (The Asia Pacific Journal Of Management Studies, 2021)
The work environment is not conducive, employees are grouped according to interests, qualified to form strong group unit brigades, making it difficult for employees outside the group to work well, carry out their duties and functions. Another thing that was found was that there was unhealthy competition between groups, showing the strength of one group to another. This study uses a quantitative survey research method using regression analysis techniques. There is an influence between the work environment on performance. This shows that an increase in the work environment will result in an increase in employee performance. There is an influence between job satisfaction on performance. This shows that an increase in job satisfaction will result in an increase in employee performance. There is an influence between work motivation on performance. This shows that an increase in work motivation will result in an increase in employee performance. There is an effect of work environment, job satisfaction and work motivation together on performance. This shows that an increase in the work environment, job satisfaction and work motivation will result in an increase in employee performance.